KEMIRINGAN OPTIMUM UNTUK TIGA PITCH MODEL TURBIN ULIR DUA BLADE SEBAGAI PEMBANGKIT LISTRIK PADA ALIRAN HEAD RENDAH - , ELFIDA, Prof.(Emr) Adhi Susanto, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Indonesia is rich in natural resources potential that can be used as the source of electrical energy, such as water sources that can serve micro hydro power plants. Most of the existing water sources have only small flow rate and low head, therefore the researchers tried to design a micro hydro power plants as one way that electrical energy crisis can be avoided. One alternative to micro-hydro power plant that is suitable for the Indonesia river is Screw Turbine (Archimedean Turbine). In this study the researcher tried to design the model of two-blade screw turbine that has variation of pitch distance (Î) and different shaft slope (K). The objective of this research is to find the optimum pitch distance (Î) and slope (K) of two-blade screw turbine model to generate output power of the generator, as it also to seek the influence of the corelation between each pitch to the generator output power (Pg) and to the generator efficiency (Ä±g). This research was carried out by performing experiments include the planning, creation tools, as well as testing equipment, and get the analysis results used for the conclusion of screw turbine model optimization that have variation pitch distance and shaft slope. The two blade screw turbine model is made with variations of pitch of 2Râ, 1.6Râ and 1.2Râ. The shaft slope variations (K) are from 25 â° to 45 â°. The study was conducted at the Laboratory of Hydroulics of Civil Engineering Diploma of Gadjah Mada University which is located at Jl. Yakasanda, Sekip, Yogyakarta. And, calculation of the dimensions of the screw turbine model refers to the theories of Rorres. The results of this research show that the best performance of two-blade screw turbines models that generate the highest generator output power (Pg) occurs at the angle of 35â° and generator efficiency (Î·g) were generated by the pitch distance of 1.2Ro.